A Review of English Language Teacher Training Programmes in Bangladesh (International Journal of Language, Literacy and Translation, 2025)
This paper reviewed the contents and objectives of three English language teacher education programmes offered by government and non-governmental organizations to in-service secondary school teachers in Bangladesh. Semi-structured interviews were used to collect additional data from the programme coordinators who were trainers as well. The aim of the study was to find out whether the training programmes created opportunities for teachers to engage in critical reflection on their own beliefs in order to develop a critical approach towards their teaching. Hence, this study drew on the extensive literature on teacher beliefs and critical reflection to advocate the need for designing teacher development programmes which focus on these two aspects. The study sought to establish the advantages of helping teachers to articulate their beliefs so that they can themselves identify whether their beliefs are in sync with language education today. This can be possible only if teachers reflect on their core beliefs about teaching that propel them to teach in a particular way. The study found that the training programmes which were reviewed all focused on classroom practices. None of the programmes focused on helping teachers to articulate or identify their beliefs so that their awareness of their own beliefs could help them appreciate the need for implementing what they were being trained to do in the classroom. It was argued that if teacher development programmes created opportunities for teachers to collectively and critically reflect on their pre-existing beliefs, it could help them use their newly acquired skills more effectively and convincingly.